Pengembangan Lembar Kerja Peserta Didik Elektronik Berbasis Mobile Learning Model Inkuiri Terbimbing pada Materi Hukum Newton - Ira Lelita Eriyanti; Jumadi; Yanarti; Wiwin Rosiningtias; Hanna Zulfaria (Jurnal Penelitian Pendidikan IPA, 2023)
Education is an endeavour to infuse civilization in the lives of individuals so that they can reach their greatest potential as human beings. Individuals are expected to be able to monitor the advancement of science and technology, as well as science and information and communication technology, through education. As a consequence, the study's goals are to establish the outcomes of the e-requirements Student Worksheets analysis, define the feasibility level of guided inquiry-based e-SW; and determine guided inquiry-based e-practicality. Electronic Student Worksheets in this study focuses on the e-SW, which is based on guided inquiry. Six media and materials professionals, one physics instructor, and 24 students took part in this project. The steps of ADDIE development are used as a research technique, comprising analysis, design, development, and implementation, however the assessment stage is not completed. The findings of this research led to the conclusion that educational product creation is viable and practicable. This is based on the results of a validation test conducted by media and material experts that scored above 80% in the very excellent category. And as well as a poll of teacher and student responses that scored above 90% in the very excellent category.